Aplikasi Kebangkrutan dengan Menggunakan Metode Altman Z-Score (Studi pada PT Jaya Agra Wattie Tbk Periode 2010-2019) - Salma Istiqomah; Ruhadi Ruhadi; Diharpi Herli Setyowati (Indonesian Journal of Economics and Management, 2021)
This research aim is to know the condition of the finance in PT Jaya Agra Wattie Tbk on 2010 – 2018. This research is used by the Altman Method. This method usually use for bankrupt analysis. After finishing the research, the company will able to know the condition of the finance and also will make the right policy. Also, it has known the condition of company finance in the beginning and be able to anticipate a finance problem which will happen in the future. It is used the secondary data which is a finance report of PT Jaya Agra Wattie. The data is taken from the official website of the company in 2010 – 2018. The result of this research shows that PT Jaya Agra Wattie is in the bankrupt condition (grey area) in 2010 to 2012 because of the result of the Zero Score has showed in between 2.6 to 1.11. So, it has the average Zero score 2.519153. Meanwhile, in 2013 to 2018 the finance of the company has in the low condition that has the average Zero Score -0.41076. The score has in bankrupt area (financial distress) with the clarification Zero Score in the low of 1.11.